2010
DOI: 10.1038/modpathol.2010.54
|View full text |Cite
|
Sign up to set email alerts
|

S100A13 is a new angiogenic marker in human melanoma

Abstract: Angiogenesis is critical in melanoma progression and metastasis and relies on the synthesis and release of proangiogenic molecules such as vascular endothelial growth factor (VEGF)-A and fibroblast growth factors (FGFs). S100A13 is a small calcium-binding protein that facilitates the release of FGF-1, the prototype of the FGF family. S100A13 is upregulated in astrocytic gliomas, in which it correlates with VEGF-A expression, microvessel density and tumor grading, and promotes a more aggressive, invasive phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 34 publications
0
64
1
Order By: Relevance
“…S10AD (S100A13). S10AD has been proposed to play roles in the invasiveness of lung cancer cells [117] and in angiogenesis of human melanoma [118]. In our tissues we found two isoforms of it, one of which ubiquitous, showing a fold increase of almost 2x, and the second, more basic, expressed sporadically.…”
Section: S10ab (S100-a11mentioning
confidence: 60%
See 1 more Smart Citation
“…S10AD (S100A13). S10AD has been proposed to play roles in the invasiveness of lung cancer cells [117] and in angiogenesis of human melanoma [118]. In our tissues we found two isoforms of it, one of which ubiquitous, showing a fold increase of almost 2x, and the second, more basic, expressed sporadically.…”
Section: S10ab (S100-a11mentioning
confidence: 60%
“…As previously reported, the S100AD in our tumor tissues displays two isoforms, the first is ubiquitous with a fold increase of about 2x with respect to the normal tissues (when present), while the second, more basic, was detected sporadically in tumor but it was absent in the normal tissues. The functional role of this S100 protein has been already discussed [117,118].…”
Section: S100a7 (S100a7)mentioning
confidence: 99%
“…S100A13, another promising prognostic marker for melanoma, is proposed to be an indicator of the angiogenic switch that facilitates disease progression. Massi and colleagues found expression in dysplastic nevi and in primary and metastatic melanoma with increasingly higher correlation in more aggressive and/or advanced tumors (Breslow thickness and Clark' s level) (64). A proteomics study reported S100A13 to be elevated in cisplatin-resistant melanoma cell lines (65).…”
Section: S100 Proteinsmentioning
confidence: 99%
“…S100A4, also called metastasis-associated protein, is universally overexpressed in a variety of tumor entities and is an independent marker for tumor progression, invasion, metastasis, poor survival, and prognosis (1). S100A4 influences cell motility, inflammation, angiogenesis, and apoptosis due to interaction between tumor cells and their microenvironment (59)(60)(61)(62)(63)(64). However, extracellular S100A4 seems to be of major importance in this context and, therefore, may possibly serve as a blood marker.…”
Section: S100 Proteinsmentioning
confidence: 99%
“…S100A13 is a small calcium (Ca2+) binding protein belonging to the S100 family and the C‐terminus of the S100A13 protein ends with a special motif, which has also been observed in metastasis‐associated proteins S100A4 and S100A10 . S100A13 is upregulated in human astrocytic gliomas and melanoma, where it correlates with VEGF‐A and FGF‐1 expression and angiogenesis, and is also associated with a more aggressive, invasive phenotype in lung cancer‐derived cell lines . To our knowledge no previous studies have investigated a correlation between S100A13 and angiogenesis and prognosis in surgically resected early‐stage NSCLC.…”
Section: Introductionmentioning
confidence: 99%